2003
DOI: 10.1002/jmor.10129
|View full text |Cite
|
Sign up to set email alerts
|

Cranial osteology in momotidae (Aves: Coraciiformes)

Abstract: Momotidae (motmots) is found throughout Latin America between Mexico and northern Argentina. Given the absence of detailed studies of cranial osteology of Momotidae in the literature, this article presents a comprehensive description of the variation of the cranial osteology in all nine species of Momotidae and compares the results with published studies of other families of Coraciiformes and families in other orders. In addition, the cranial structures described are related to ecological and behavioral aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
14

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 15 publications
(30 reference statements)
1
9
1
14
Order By: Relevance
“…The latter authors added that the orbital process in fowl fused with the zygomatic process of temporal bone.Unlike [9] that reported there are frontal, lacrimal and cranial processes of lacrimal bone that formed the cranioventral margin of the orbit. In the same line with [8] that added there was a small lacrimal bone in fowl and pigeon and large in duck and geese, but the present study revealed no movable joint between the lacrimal and nasal bone.Similar to [12,13] in ostrich and [14] in Baryphthengus ruficapillus, the same structures and articulations of the quadrate bone were noticed. However, different result was cleared by [9] who clarified that, the otic process articulated with the zygomatic process…”
Section: Discussionsupporting
confidence: 84%
“…The latter authors added that the orbital process in fowl fused with the zygomatic process of temporal bone.Unlike [9] that reported there are frontal, lacrimal and cranial processes of lacrimal bone that formed the cranioventral margin of the orbit. In the same line with [8] that added there was a small lacrimal bone in fowl and pigeon and large in duck and geese, but the present study revealed no movable joint between the lacrimal and nasal bone.Similar to [12,13] in ostrich and [14] in Baryphthengus ruficapillus, the same structures and articulations of the quadrate bone were noticed. However, different result was cleared by [9] who clarified that, the otic process articulated with the zygomatic process…”
Section: Discussionsupporting
confidence: 84%
“…A metodologia adotada para o estudo da osteologia craniana segue aquela descrita por PASCOTTO & DONATELLI (2003). Para medidas e comparações de determinadas estruturas cranianas, foi utilizado um paquímetro digital Mitutoyo 500-143B, com capacidade de resolução de 0,01mm a 150mm.…”
Section: Methodsunclassified
“…O termo "processo zigomático" adotado por BAUMEL & WITMER (1993) e utilizado por PASCOTTO & DONATELLI (2003) foi aqui substituído pelo termo processo esquamosal, como sugerido por JOLLIE (1957) e seguido por outros autores (HÖFLING & GASC 1984, DONATELLI 1992, 1996, POSSO & DONATELLI 2006, pelo fato do termo zigomático estar associado ao arco zigomático dos mamíferos. O termo "lobos parietais", também sugerido por BAUMEL & WITMER (1993) e utilizado por PASCOTTO & DONATELLI (2003), segue a proposição de POSSO & DONATELLI (2006) que, por meio da análise de espécimes de cucos (Cuculiformes) jovens, diagnosticou a participação do osso frontal na formação dos lobos parietais devendo a região, portanto, ser denominada de "prominentia frontoparietalis".…”
Section: Methodsunclassified
See 2 more Smart Citations